Studi Literatur: Potensi Tanaman Belimbing Wuluh dalam Menurunkan Tekanan Darah Penderita Hipertensi - Ahmad Yani; Venny Patricia (Politeknik Kesehatan Kemenkes Mamuju, 2022)
The high prevalence of hypertension still encourages research to find blood pressure-lowering drugs, especially those derived from natural ingredients. One of the plants that have been reported to have the potential to reduce blood pressure is the bilimbi (Averrhoa bilimbi L.). Observations of the antihypertensive activity of this plant have been carried out, both from the use of leaves and fruit. However, several existing studies have shown that the dose of using the leaves and fruit of bilimbi still varies with varying levels of effectiveness, so the effective dose of this plant utilization remains unknown. This study aims to see the efficacy of bilimbi in lowering blood pressure and determine the most effective dose for its use. The literature selection was carried out by searching the Google Scholar database, the Garba Rujukan Digital portal (Garuda), ScienceDirect, Pubmed, and Directory Open Access Journals (DOAJ) using predetermined keywords. Then, the identification and screening of articles based on duplication and inclusion criteria were carried out. The study results showed that the fruit had higher effectiveness in lowering blood pressure than the leaves. This literature study concluded that consuming 100 ml of bilimbi fruit juice regularly for 14 days may lower the blood pressure up to 34 mmHg.